Annual Plan 1971-72, Narrative - Planning Commission (Planning Commission, 1971)
The Annual Plan hag essentially to be a part of the Fourth Five Year Plan and has to keep up the tempo of progress which has been attained during the past two years in respect of the schemes included in the Five Year Plan. The process of Planning envisages a progressive rise in expenditure to sustain the improvement in the living standard of the people. There has, therefore, to be some further acceleration in the developmental activity necessarily requiring a higher outlay.
Planning Commission